Romancing the wind: The role of gales in the Anglo-Saxon Chronicle - Marilina Cesario (Filologia Germanica)
The Anglo-Saxon chroniclers’ interest in eclipses, comets, and other celestial phenomena undoubtedly derives from classical and continental annals, but the recording of the wind in association with human affairs is quite exceptional. The wind is noted twelve times in the AngloSaxon Chronicle, between the years 1009 and 1123, but there is no mention of it in the “common stock”. This article investigates the role of the wind in the Anglo-Saxon Chronicle and examines whether the Anglo-Saxon annalists’ awareness of the meteorological phenomenon was prompted by the dissemination of computistical materials. These included Easter tables, treatises on natural science, texts and diagrams on the direction and/or names of winds, weather prognostics and prognostication by the wind, which reached England from Fleury during the Benedictine Reform. This study will also consider whether there was a correlation, a cause and effect relationship, between the wind and the events narrated.